The Effectiveness of Pharmacist Interventions on Cardiovascular Risk: The Multicenter Randomized Controlled RxEACH Trial - Tsuyuki, Ross T; Al Hamarneh, Yazid N; Jones, Charlotte A; Hemmelgarn, Brenda R (Journal of the American College of Cardiology, 2016)
Despite the cardiovascular disease (CVD) risk associated with hypertension, diabetes, dyslipidemia, and smoking, these risk factors remain poorly identified and controlled. The study sought to evaluate the effectiveness of a community pharmacy-based case finding and intervention on cardiovascular risk. The RxEACH (Alberta Vascular Risk Reduction Community Pharmacy Project) study was a randomized trial conducted in 56 community pharmacies. Participants were recruited by their pharmacist, who enrolled adults at high risk for CVD. Patients were randomized to usual care (usual pharmacist care with no specific intervention) or intervention, comprising a Medication Therapy Management review from their pharmacist and CVD risk assessment and education. Pharmacists prescribed medications and ordered laboratory tests as per their scope of practice to achieve treatment targets. Subjects received monthly follow-up visits for 3 months. The primary outcome was difference in change in estimated CVD risk between groups at 3 months. CVD risk was estimated using the greater of the Framingham, International, or United Kingdom Prospective Diabetes Study risk scores. We enrolled 723 patients (mean 62 years of age; 58% male, and 27% smokers). After adjusting for baseline values and center effect, there was a 21% difference in change in risk for CVD events (p < 0.001) between the intervention and usual care groups. The intervention group had greater improvements in low-density lipoprotein cholesterol (-0.2 mmol/l; p < 0.001), systolic blood pressure (-9.37 mm Hg; p < 0.001), glycosylated hemoglobin (-0.92%; p < 0.001), and smoking cessation (20.2%; p = 0.002). The RxEACH study was the first large randomized trial of CVD risk reduction by community pharmacists, demonstrating a significant reduction in risk for CVD events. Engagement of community pharmacists with an expanded scope of practice could have significant public health implications. (The Alberta Vascular Risk Reduction Community Pharmacy Project: RxEACH [RxEACH]; NCT01979471).